Developing a High School Mental Health Action Checklist in Thailand: insights on perception and communication - Punneng, Suwatsa; Arphorn, Sara; Thanachoksawang, Chatchai; Bangkadanara, Goontalee; Tangtong, Chaiyanun; Maruo, Suchinda Jarupat; Chantra, Niranyakarn; Yogyorn, Densak; Ishimaru, Tomohiro (Frontiers in Public Health, 2024)
Background This study aimed to develop a mental health action checklist for high school students that emphasized the importance of readiness, safety, and good hygiene at work to enhance their mental health and prepare them for the workforce. Methods In total, 949 students from public high schools in Bangkok, Thailand voluntarily participated in this study. The 15-item High School Mental Health Action Checklist was developed based on a literature review and a pilot study. We used the index of item-objective congruence (IOC) to verify the content validity of the Checklist and exploratory factor analysis (EFA) to establish its construct validity. The tool’s internal consistency was estimated using Cronbach’s alpha coefficient. Results The High School Mental Health Action Checklist had good content (IOC = 0.867) and construct validity. EFA revealed four factors that accounted for 46.5% of the variance. The overall reliability coefficient for the High School Mental Health Action Checklist was 0.788, and the reliability coefficients of the subdomains were 0.783–0.797. Conclusion The Checklist will allow schools to develop an annual action plan for student mental health promotion activities, in accordance with public health guidelines. Our results indicate the High School Student Mental Health Action Checklist has good psychometric properties.